MANAGEMENT OF VILLAGE FUND ALLOCATION IN KAMPUNG FAFI MARIAT DISTRICT OF SORONG REGENCY - Kadir, Muhammad Arifin Abd; Suaib, Hermanto; Hardiyanti, Putri (Natapraja, 2021)
Planning and implementation of Village Fund Allocation activities, has shown an accountable and transparent management. Meanwhile, in terms of accountability, the physical results have shown an accountable and transparent implementation, but from the administrative side, further guidance is still needed, because it is not fully in accordance with the provisions. The main obstacle is the ineffectiveness of fostering village government officials and human resource competencies, so that they still need assistance from local government officials on an ongoing basis. This study aims to describe the management of village funds in terms of the management of village fund allocations that have not been in accordance with applicable regulations. The research method using qualitative. Data collection techniques by observation, interviews, and documentation. Data analysis techniques, the data collected in this study, both primary data and secondary data were re-examined in order to determine the completeness of the data obtained. The results of this study indicate that for the planning and implementation of development activities, community empowerment in Fafi Village, Mariat District which utilizes village funds, lacks optimization of management, but in terms of being responsible for the physical results and effectiveness of the use of development that is felt by the community is also lacking. The main obstacles in utilizing village funds in Fafi Village, Mariat District, Sorong Regency are inadequate infrastructure and lack of socialization to the community so that they still need assistance from the District Government officials on an ongoing basis.